Strategi Keberlanjutan Usaha Hidroponik Green House Jawa Timur Dengan Analytical Hierarchy Process (AHP): East Java Green House Hydroponic Business Sustainability Strategy Using The Analytical Hierarchy Process (AHP) - Hermawan, Fendi; Sundari, Sri; Kustiari, Tanti; Agustinus Waluyo, Donny; Hartatie, Dian; Mayasari, Financia; Arief Putranto, Hermawan (Politeknik Negeri Jember, 2024)
The Smart Farming concept is identical to the hydroponic cultivation system which is a new revolution in agricultural cultivation methods. Hydroponics is also known as soilless culture, which is a cultivation method that does not use soil as a medium to support plant growth. The advantages of hydroponic greenhouse cultivation include higher yields, the microclimate can be controlled and can be carried out throughout the year without paying attention to weather conditions, so that plant productivity is increased. Apart from the advantages that hydroponic greenhouse cultivation has, it has the potential to increase productivity as described above, the market prospects for the results of hydroponic cultivation are also very promising. The aim of this research is to analyze sustainability and priority strategies in efforts to develop green house hydroponic cultivation using the Analytical Hierarchy Process (AHP). This research was conducted in East Java. The results of the analysis show that the most dominant factors that are attributes of sustainability levers are the level of waste management, sales price stability, community conflict, the level of application of modern technology and partnership patterns. The results of the Analytical Hierarchy Process (AHP) analysis show that the priority strategy that can be implemented is the implementation of a partnership pattern with the highest value of 0.445.